Efecto de las prácticas precosecha (desmane y utilización de protectores) sobre los rendimientos del cultivo de banano (Mussa acuminata S) provincia de Los Ríos. - Basurto Rendón, María Deidama (2008)
The present investigation is carried out it in the dry time of the year 2007 among the months on September to December of the year same, in an established plantation of banana Williams of the group Cavendish; of the farm "Clementine", located in Babahoyo, Province of The Rios, with the purpose of study the behavior of the protectors' productivity with desmane. The factors in study were, desmane (false + 2 and false + 3) and protectives (daipa and protective disk ) you uses a design totally at random (D.C.A ) with four repetitions and five treatments of whose useful areas information was obtained to evaluates variables of productivity (statistic) and the development of the clusters (complementary) of the experimental material. Regarding the variables evaluated statistically, (calibration of the second hand, calibration of the ultimate hand, weight of the cluster longitude of fingers, conversion and waste). He/she was proven that the opposing differences respond fundamentally to the influence of the factor desmane, standing out among them the false one + 3 that it reaches the best averages for the variables, calibration of the second hand, calibration of the ultimate hand, with of the cluster longitude of fingers, conversion, and waste. As for the first group of variables (week of it sheathes, week of desmane, number of hands, week of protection and week of crop) you could verify that influence of the conditions agroclimaticas exists in the development of the rehearsal. The protectives with factor in study was a influence publicly known specifically in the variables, conversion and waste respectively combinated the levels of the factors in study, stablish with best option statistic the treatment F3 B (false + 3 with protective disk), and from the point of see economic the treatment F3 A (false + 3 with daipa), giving an avaluation .of return marginal of 43.20%.